Emerging role of γδ T cells in vaccine‐mediated protection from infectious diseases. Issue 8 (28th August 2019) - Dantzler, Kathleen W; de la Parte, Lauren; Jagannathan, Prasanna
Abstract: γδ T cells are fascinating cells that bridge the innate and adaptive immune systems. They have long been known to proliferate rapidly following infection; however, the identity of the specific γδ T cell subsets proliferating and the role of this expansion in protection from disease have only been explored more recently. Several recent studies have investigated γδ T‐cell responses to vaccines targeting infections such as Mycobacterium, Plasmodium and influenza, and studies in animal models have provided further insight into the association of these responses with improved clinical outcomes. In this review, we examine the evidence for a role for γδ T cells in vaccine‐induced protection against various bacterial, protozoan and viral infections. We further discuss results suggesting potential mechanisms for protection, including cytokine‐mediated direct and indirect killing of infected cells, and highlight remaining open questions in the field. Finally, building on current efforts to integrate strategies targeting γδ T cells into immunotherapies for cancer, we discuss potential approaches to improve vaccines for infectious diseases by inducing γδ T‐cell activation and cytotoxicity. Abstract : It has long been known that several γδ T‐cell subsets rapidly increase in number following systemic infections and are able to perform numerous roles, including direct anti‐microbial roles, recruitment of innate immune cells and activation of adaptive immune cells. However, whether these cells represent an important mediator of protection that could be targeted via vaccination has been unclear. In this manuscript, we review evidence indicating that γδ T cells may play an important role in mediating vaccine‐induced protection to several bacterial, protozoan and viral infections. Image created with Biorender.com.